Establishment of Democratic Regional Regulations in Bandung District - Nindhiawati, Nia (KnE Social Sciences, 2023)
This research was conducted in Bandung Regency. The formation of democratic regional regulations by the Bandung Regency government has not been implemented democratically because community participation, as a form of democracy in the process of forming regional regulations, is only ceremonial. As a result, the space for the community to participate in responding or directly criticizing a regional policy packaged in regional regulations cannot be fully utilized. Several factors influence the formation of regional regulations. One of the main factors is the legal structure, where the Regional Government and DPRD do not provide sufficient space for the community to express their aspirations. The time allocated for discussing the legal substance during the process is also very limited, which hinders the full application of democratic principles as outlined in the Act. The research utilized an empirical approach with direct research and was documented as it is. It was found that the formation of legislation in the region is still relatively limited because the publication of regional regulations to the public is not considered a necessity. Additionally, the legal culture of the community, particularly community participation, is still poorly understood and needs further development. Keywords: regional regulations, democratic, local government